Habitat Preference of Great-Spotted Woodpecker (Dendrocopos major Linnaeus, 1758) and Lesser-Spotted Woodpecker (Dendrocopos minor Linnaeus, 1758) in the Presence of Invasive Plant Species - Preliminary Study - Ónodi G´bor (Sciendo, 2014)
This study was carried out in Hungary, in an old, unmanaged, riparian poplar-willow forest, where two invasive tree species, the green ash and the boxelder maple are presented and reproduce more effectively therefore are more abundant than the native species in the study area. There are also invasive hybrid wild grapes to be found. These invasive plants cause widespread problems in floodplain forests in Central Europe. We studied Great-spotted and Lesser-spotted Woodpeckers. We investigated the following questions: Which tree species are preferred by the foraging birds? How are the foraging birds distributed spatially between the microhabitats? Are there any differences in terms of foraging niche utilization between the two studied species? We gathered our data through weekly standard observations throughout two whole years. Based on our findings we could determine that both species preferred the less abundant native trees rather than the invasive ash and maple trees, though Lesser-spotted Woodpeckers preferred hybrid wild grapes the most. Great-spotted Woodpeckers preferred the middle heights of the trees, they also moved mainly on trunks. Lesser-spotted Woodpeckers used the thinnest branches in the canopy. Based on our results we predict that the decrease of the native tree species may create a suboptimal habitat compared to the current situation. As the studied species are the major cavity excavators, the above mentioned changes will probably have significant effects on numerous cavity dependent species.